2009
DOI: 10.1177/1352458508098373
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in multiple sclerosis is associated with the disruption of frontal and parietal pathways

Abstract: Our results suggest that the symptom of fatigue is associated with a disruption of brain networks involved in cognitive/attentional processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
180
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(198 citation statements)
references
References 40 publications
11
180
1
6
Order By: Relevance
“…Recently, Sepulcre et al 30 showed an association between atrophy of the superior frontal sulcus and middle frontal sulcus and fatigue severity in a heterogeneous groups of patients with MS, including patients with clinically isolated syndromes suggestive of MS and those with the progressive forms of the disease. These authors suggested that such a regional distribution of atrophy in patients with fatigued MS might be related to retrograde degeneration of axons passing through WM lesions, because these patients had a higher occurrence of lesions in regions of the frontal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sepulcre et al 30 showed an association between atrophy of the superior frontal sulcus and middle frontal sulcus and fatigue severity in a heterogeneous groups of patients with MS, including patients with clinically isolated syndromes suggestive of MS and those with the progressive forms of the disease. These authors suggested that such a regional distribution of atrophy in patients with fatigued MS might be related to retrograde degeneration of axons passing through WM lesions, because these patients had a higher occurrence of lesions in regions of the frontal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…In different clinical populations, fatigue has been linked, albeit inconsistently, with alterations in a host of different brain structures, such as the monoaminergic nuclei, 25 the ascending reticular formation, 26 and the frontostriatal network. 2,27 The heterogeneity of these findings could be related to the different patients population studied, the subjectivity of fatigue perception complaint, or the effect of multiple confounding factors such as mood, disease duration, education, and age.…”
mentioning
confidence: 99%
“…16,27 In our study, the relationship between vmPFC lesions and fatigue was first illustrated by a lesion Figure 1 Overlap map of lesioned areas in fatigued penetrating brain injury subjects…”
mentioning
confidence: 99%
“…55 In patients with RRMS and SPMS, temporal lobe atrophy is associated with auditory/verbal memory and visual/spatial memory performance, 56 while hippocampal atrophy is related to a poor performance in memory-encoding tasks. 57 Fatigued patients with MS experience GM atrophy in frontal regions, 58 while those with cerebellar dysfunction have a reduced cerebellar GM volume compared with those without. 59 In patients with MS with longstanding disease or severe disability, focal thinning of the primary SMC has been reported.…”
mentioning
confidence: 99%